2022
DOI: 10.3390/v14102177
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological and Epidemiological Findings in Pet Cats Naturally Infected with Feline Immunodeficiency Virus (FIV) in Australia

Abstract: Feline immunodeficiency virus (FIV) infection in experimentally infected domestic cats produces characteristic clinical manifestations including hematological changes, neurological disease, neoplasia (most notably lymphoma) and lymphopenia-mediated immunodeficiency predisposing cats to a range of secondary infections. Conflicting reports exist, however, with regard to disease associations and survival time in naturally FIV-infected cats. The purpose of this retrospective case–control study was to investigate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…In fact, SAA is a feline major positive APP [ 6 , 53 ], protecting tissues from excessive damage induced by inflammation and acting to regulate the inflammatory process and the immune response [ 54 , 55 ]. Hyperglobulinemia can be observed in both feline inflammatory [ 30 , 31 ] and infectious diseases [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. Furthermore, in the serum protein electrophoretic evaluation, most of the positive APPs migrate as alpha- or beta-globulins, and immunoglobulins are beta- and gamma-globulins; thus, a globulin increase can give information about the presence of inflammatory and immune-mediated conditions [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, SAA is a feline major positive APP [ 6 , 53 ], protecting tissues from excessive damage induced by inflammation and acting to regulate the inflammatory process and the immune response [ 54 , 55 ]. Hyperglobulinemia can be observed in both feline inflammatory [ 30 , 31 ] and infectious diseases [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. Furthermore, in the serum protein electrophoretic evaluation, most of the positive APPs migrate as alpha- or beta-globulins, and immunoglobulins are beta- and gamma-globulins; thus, a globulin increase can give information about the presence of inflammatory and immune-mediated conditions [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…In cats, serum amyloid A (SAA) and α-1-acid glycoprotein (AGP) are major APPs, haptoglobin is a moderate APP, and C- reactive protein and ceruloplasmin are minor APPs [ 6 ]. Most APPs are globulins, and hyperglobulinemia also reflects the increased production of other proteins, particularly immunoglobulins, that can be observed in both inflammatory non-infectious [ 30 , 31 ] and infectious diseases [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. Moreover, the albumin-to-globulin ratio (AGR), routinely reported in the biochemical profile, is considered a screening marker for dysproteinemia observed in feline inflammatory conditions [ 34 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is controversy regarding the clinical relevance of FIV in naturally infected cats [ 14 ] as some investigators believe that FIV itself does not cause severe clinical disease, and FIV-infected cats live many years without any health problems [ 15 ]. Early epidemiological studies suggested environmental factors such as indoor housing versus outdoor free-roaming status impacted FIV infection status [ 16 ].…”
Section: Introductionmentioning
confidence: 99%